Analysis of South Korea’s Cultural Policies during COVID-19 Pandemic (2020-2022) - Kembaren, Elisabeth Ermuliana; Febriani, Annisa Indah (Bina Nusantara University, 2025)
This article examines South Korea's cultural policies in response to the Covid-19 pandemic (2020-2022). This study uses a qualitative method which mainly originates from various press releases, publications and annual reports that are officially uploaded by the Ministry of South Korea. The study's findings show that the South Korean government consistently implemented a variety of cultural policies during the three-year pandemic period, including pandemic control, funding, increased consumption, lobbying, policy discussions, job creation, and training. However, cultural art stakeholders play an important role in shaping cultural policies during this time.